A Highly Sensitive Electrochemical Sensor System to Detect and Distinguish Between Glyphosate and Glufosinate. Issue 5 (27th May 2021) - Dhamu, Vikram Narayanan; Poudyal, Durgasha C.; Muthukumar, Sriram; Prasad, Shalini
Abstract : Glyphosate and Glufosinate are widely used herbicides worldwide for controlling weeds in the agriculture field. The large increase in the herbicides tolerant plants has dramatically affected the level of usage of these herbicides recently. With the growing alarm about the associated toxicity to the environmental and human health, there is a need for direct low concentration detection of these herbicides present at the various food crops products and water. In this work, we present a simple electrochemical sensor to selectively detect glyphosate in presence of Glufosinate a structurally similar phosphorus containing amino acid group. The sensor substrate is made up of an interdigitated Au microelectrode, which was immobilized with glyphosate antibody, bounded with the help of the Dithiobis (succinimidyl propionate) (DSP) crosslinker. The data obtained using non-faradaic EIS method, showed a linear range across the whole dosing interval-10 ng ml −1 to 50 ug ml −1 for glyphosate in presence of the interfering component Glufosinate with the detection limit of 10 ng ml −1 and the sensitivity of 1.323% (change in impedance)/ppb. Further the sensor has been proven to measure the spiked pesticides doses in real oatmeal samples. Such micro-volume, high-sensitive, and selective platform which requires no prior sample preparation can be a potentially game-changing electrochemical on-field sensing device to measure the threshold limit, a precautionary step to alert the common man using the food products and farmers working in the agriculture field.